Postharvest strategies for preventing flower wilting and leaf yellowing in cut Ranunculus flowers - Cavallaro, Viviana; Bulgari, Roberta; Florio, Francesco Elia; Restuccia, Pasquale; Vinci, Gianluca; Guffanti, Davide; Vignati, Sara; Ferrante, Antonio (Frontiers in Horticulture, 2023)
Introduction Appropriate postharvest treatment, as well as adequate conditions of storage, can be adopted to elongate the lifespan of cut flowers. Thidiazuron (TDZ), a substituted phenylurea, and 1-methylcycloproene (1-MCP), a non-toxic inhibitor of ethylene perception, are nowadays substances commonly used to prevent early damage caused by senescence and to delay chlorophyll degradation. Ranunculus asiaticus L. is cultivated for cut flower production and is highly sensitive to ethylene and leaf yellowing. In this study, the effect of different pulse-tratment in prolonging cut ranunculus vase life was analyzed. Methods TDZ 10 µM, 1-MCP 500 ppb, and a combination of both were applied for 24 hours after harvest. The effect of the treatments was evaluated by performing non-destructive (% loss of fresh weight, chlorophyll a fluorescence, in vivo chlorophyll content, and Nitrogen Flavonol Index – NFI) and destructive (chlorophyll, carotenoids, anthocyanins concentration, and phenolic index) analyses at 0, 1, 12, and 14 days from treatments. Results and Discussion Flower wilting was delayed by 4 days in 1-MCP + TDZ 10 µM treatments, which also reduced weight loss and chlorophyll degradation compared to controls. The effectiveness of these compounds in preventing senescence has been confirmed by the decreased biosynthesis of phenolic compounds.